The Effect of Selfish Ethics, Altruist Ethics, and Morality on Taxpayer Compliance with Trust as a Moderating Variable - Yudi Hermawan; Lilis Ardini; David Efendi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine egoistic ethics, altruistic ethics, and morality in explaining taxpayer compliance. This study also tests the effect of trust as a moderating variable. By using the Slippery Slope Theory and the Theory of Planned Behavior, this study aims to empirically prove the taxpayer compliance model. This study is quantitative with a survey approach to individual taxpayers. The population is individual taxpayers registered at the Pratama Tax Office, with a sample of 143 respondents. The results of the hypothesis test show that empirically, egoistic ethics has a negative effect on taxpayer compliance, while morality does not have a significant effect. In addition, the effect of trust as a moderating variable can strengthen the effect of altruistic ethics on taxpayer compliance and can also weaken the effect of egoistic ethics on taxpayer compliance.